Contribution of sustainable street vending to municipal solid waste management in Tanzania : A case of Morogoro municipality - Apolo, Didas (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the degree of Masters of Science in Environmental Management (MSc. EM) of Mzumbe University